GENDER EQUALITY IN UKRAINE: ANALYSIS OF LEGAL ACTS - BakumenkoО.; Kashaba, O.; Shcherbyna, I. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
Today, in most countries, the equal legal status of women and men, as well as the equal opportunity to execute it in society, that is, gender equality, has long been a commonplace in public discourse and politics. In Ukraine, equality between men and women is declared at the constitutional level, which testifies to the approach of the Ukrainian state and civil society to the European and world level of solving gender problems. The execution of the legal regulation of the state gender policy in Ukraine is considered by the normative legal acts of two levels: supranational and national and the results of their implementation. The actual problem of not only creating a sufficient regulatory and legal field, but also its compliance is analyzed. Moreover, attention is paid to the facts of violation and neglect of the current legislation, which in turn leads to the preservation of gender inequality in Ukrainian society, where most property, power and general influence belong to men. There is a need to develop a new paradigm of state power, which should envisage the optimal use of human resources, in particular its female component and, ultimately, the achievement of gender equality as an important part of the development strategy, which is intended to enable all men and women to improve their living standards. It is argued that the relevance of gender equality in the contemporary historical context will be maintained in the short term. This is due to the fact that the problems of gender inequality, and therefore of socio-economic and political discrimination against women, cannot be solved solely by state reforms, since a system of rules that forbid any deterioration of women’s rights is unlikely to operate without an effective system for monitoring of norms implementation.